Fairness perceptions and voluntary tax compliance in Nigeria: The moderating role of trust - Ya’u, Abba; Saad, Natrah (Othman Yeop Abdullah Graduate School of Business, 2019)
Fairness perception in Nigeria has been a subject of concern. Further, the study examined the moderating role of trust in explaining voluntary tax compliance in Nigeria. For that purpose, a cross-sectional study was conducted. 249 questionnaires were collected from the 450 questionnaires issued to the owners of micro-enterprises in Jigawa State Nigeria. The data was analyzed using SPSS and PLS to answer the research questions. The Partial Least Square (PLS) path modeling was used in examining the relationship between fairness perceptions and voluntary tax compliance, trust and voluntary tax compliance and the moderating role of trust between fairness perception and voluntary tax compliance. Moreover, the results reveal that fairness perceptions have a positive and significant relationship on voluntary tax compliance and trust in authority has significant and positive relationships with voluntary tax compliance. Additionally, trust moderates the relationship between fairness perceptions and voluntary tax compliance. The study has the potential highlight to the Nigerian government on the way to improve voluntary tax compliance among citizens. The study also contributes to the paucity of accounting literature on taxation in Nigeria and also contribute to the existing body of accounting literature as a whole.